Anti-thermal-quenching and colour-tuneable Tb3+/Ce3+-doped phosphor from natural wollastonite - Yu Xinhong; Chen Feng; Yang Ming; Ruan Min; Feng Wei (Processing and Application of Ceramics)
Series of doped natural wollastonite phosphors (xTb3+/xLi+, yCe3+/yLi+ and xTb3+/0.06Ce3+/xLi+ co-doped wollastonite) were synthesized by high temperature solid state thermal diffusion method in vacuum furnace. The powders mainly consisted of low temperature α-CaSiO3 phase corresponding to the triclinic crystal structure, and according to ionic radii differences it was proposed that Tb3+ and Ce3+ had tendency to be incorporated at the Ca2+ position. The natural wollastonite powder has primarily needle-like particles with small amount of finer spherical aggregates, whereas the portion of finer particles increases significantly after the doping with Tb3+/Ce3+ ions. Under 352 nm light excitation, the Tb3+/Li+ co-doped wollastonite phosphors with Tb3+/Li+ content between x = 0.08-0.18 achieved tuneable luminescence from green to yellow through energy transfer from Tb3+ to minor impurity Mn2+ existing in the matrix. All of the Ce3+/Li+ co-doped wollastonite phosphors with Ce3+/Li+ content between y = 0.02-0.10 emitted intense purple-blue light centred at 382 nm. In the xTb3+/0.06Ce3+/xLi+ (0.01 ≤ x ≤ 0.09) co-doped wollastonite phosphors, Ce3+ acted as a sensitizer and the energy transfer efficiency from Ce3+ to Tb3+ reached 62.5%. Temperature dependent photoluminescence within 298-498K suggested an excellent thermal stability of the 0.06Ce3+/0.06Li+ co-doped wollastonite phosphor, of which the intensity at 498 K retained 96.2% of that at room temperature. Importantly, anti-thermal-quenching phenomenon was observed in the 0.12Tb3+/0.12Li+ co-doped wollastonite phosphor, and the 545 nm emission intensity at 498 K reached 120.3%of that at 298K. The regulation of thermal luminescence behaviour for Tb3+ was achieved by incorporating Ce3+ ions in the 0.12Tb3+/0.12Li+ co-doped wollastonite phosphor. Based on the observations, the above materials display good thermal stability and can be developed as phosphors for application in display devices and LEDs above room temperature.